2008
DOI: 10.1200/jco.2007.11.9081
|View full text |Cite
|
Sign up to set email alerts
|

Risk of New Primary Nonbreast Cancers After Breast Cancer Treatment: A Dutch Population-Based Study

Abstract: Breast cancer patients diagnosed in the 1990 s experienced a small but significant excess risk of developing an SNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
182
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 44 publications
12
182
4
2
Order By: Relevance
“…Our site-specific results were broadly similar to those from a pooled analysis of 63 randomised clinical trials of breast cancer radiotherapy and several observational studies. In these studies, there was evidence of increased risks of lung (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005;Darby et al, 2005;Andersson et al, 2008;Schaapveld et al, 2008), oesophageal (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005) and contralateral breast cancer (Gao et al, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005), as well as soft tissue sarcomas (Huang and Mackillop, 2001;Clarke et al, 2005;Andersson et al, 2008), in women treated with radiotherapy compared with unirradiated women. In the pooled analysis of clinical trials , the authors did not estimate attributable risks, but it was possible to estimate them on the basis of the data presented.…”
Section: Discussionmentioning
confidence: 99%
“…Our site-specific results were broadly similar to those from a pooled analysis of 63 randomised clinical trials of breast cancer radiotherapy and several observational studies. In these studies, there was evidence of increased risks of lung (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005;Darby et al, 2005;Andersson et al, 2008;Schaapveld et al, 2008), oesophageal (Zablotska and Neugut, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005) and contralateral breast cancer (Gao et al, 2003;Roychoudhuri et al, 2004;Clarke et al, 2005), as well as soft tissue sarcomas (Huang and Mackillop, 2001;Clarke et al, 2005;Andersson et al, 2008), in women treated with radiotherapy compared with unirradiated women. In the pooled analysis of clinical trials , the authors did not estimate attributable risks, but it was possible to estimate them on the basis of the data presented.…”
Section: Discussionmentioning
confidence: 99%
“…Most of those studies addressing melanoma risk after breast cancer concerned patients treated in the distant past and therefore with treatment regimens not including hormonal therapy (15,16), or lacked antiestrogen data or when available, did not evaluate if hormonal therapy influenced melanoma risk (17,19,(20)(21)(22)24). To our knowledge, only 2 prior studies evaluated melanoma cancer risk among breast cancer patients according to hormonal therapy (23,24). The large study from the Netherlands of a population-based breast cancer cohort (23) showed an increased risk of secondary melanoma (SIR: 1.69, 95% CI: 1.44-1.97).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, only 2 prior studies evaluated melanoma cancer risk among breast cancer patients according to hormonal therapy (23,24). The large study from the Netherlands of a population-based breast cancer cohort (23) showed an increased risk of secondary melanoma (SIR: 1.69, 95% CI: 1.44-1.97). As in our study, the excess was absent in women with hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate ratios (IRR) between the treatment and corresponding non-treated group were then compared. In these calculations, patients were considered to be at risk from the date of diagnosis of the primary breast cancer until the date of diagnosis of the respective second cancer, date of death, last date on which the patient was known to be alive, or end of the study period (December 31,2003), whichever criterion occurred first. The effects of treatment on the second cancer were adjusted for covariates and analyzed with stratification by age at the first primary breast cancer, time since diagnosis of the first primary breast cancer, and type of combined treatment.…”
Section: Methodsmentioning
confidence: 99%